Effect of conventional irrigation and photoactivated disinfection on Enterococcus faecalis in root canals: An in vitro study - Balakrishna, Niyati (J Conserv Dent, 2017)
AIMS: A study was done to evaluate the antimicrobial efficacy of sodium hypochlorite (NaOCl) and photoactivated disinfection (PAD) on Enterococcus faecalis. SETTINGS AND DESIGN: Random sampling, in-vitro study. SUBJECTS AND METHODS: Access opening and biomechanical preparation were performed on fifty freshly extracted mandibular second premolars. The specimens were sterilized; 15 μm of E. faecalis was inoculated into each canal and incubated at 36°C for 24 h. Later, specimens were randomly divided into two groups of fifty each and following procedures was carried out: (i) conventional irrigation with 2.25% NaOCl (ii) PAD using diode laser, and toluidine blue photosensitizer. Samples were collected from each canal using sterile paper points which were deposited in brain heart infusion broth, and microbiological evaluation was carried out. STATISTICAL ANALYSIS USED: Student's t-test was used to find the significant difference in the reduction of colony forming unit (CFU) between the groups. RESULTS: The mean CFUs of the two groups showed statistically significant difference (P = 0.001). Improved antibacterial efficacy was seen with PAD group compared to conventional NAOCL irrigation. CONCLUSIONS: NaOCl alone was not effective in eliminating E. faecalis completely from the root canals. PAD compared to conventional irrigation showed the best results in removing E. faecalis from root canals.